Implementasi MARKAS untuk Dana BOS di Dinas Pendidikan dan Kebudayaan Pontianak: Studi Kualitatif Persepsi Pengguna - Karunia, Urai; Tantri, Sakina Nusarifa (Journal of Social and Policy Issues, 2024)
MARKAS is the only application for the Education Department to manage reporting of BOS funds based on the Joint Circular Letter (SEB) of the Ministry of Home Affairs Number 907-6479-SJ and the Ministry of Education and Culture Number 7 of 2021. This research aims to find out the users’ perception on the implementation of MARKAS in reporting Dana BOS at Education and Culture Office of Pontianak City. This research used a qualitative method with a descriptive approach. The data collection techniques used are interviews, observation, and documentation. The data analysis is carried out by reducing data, presenting data, and drawing conclusions. This study found that there are perceived ease and usefulness in using the application. Even though there are various obstacles experienced by users, the application is very influential in assisting in reporting BOS funds. The government needs to develop applications to overcome existing obstacles. It is hoped that this research can provide benefits to literature and educational materials related to the use of information technology for the development and improvement of the MARKAS application system in the future.